Systems Engineering : a Systemic and Systematic Methodology for Solving Complex Problems. - Kasser, Joseph Eli (CRC Press LLC, 2019)
This book will change the way you think about problems. It focuses on creating solutions to all sorts of complex problems by taking a practical, problem-solving approach. It discusses not only what needs to be done, but it also provides guidance and examples of how to do it. The book applies systems thinking to systems engineering and introduces several innovative concepts such as direct and indirect stakeholders and the Nine-System Model, which provides the context for the activities performed in the project, along with a framework for successful stakeholder management. A list of the figures and tables in this book is available at https://www.crcpress.com/9781138387935. FEATURES Treats systems engineering as a problem-solving methodology Describes what toolssystems engineers use and how they use them in each state of the system lifecycle Discusses the perennial problem of poor requirements, defines the grammar and structure of a requirement, and provides a template for a good imperative construction statement and the requirements for writing requirements Provides examples of bad and questionable requirements and explains the reasons why they are bad and questionable Introduces new concepts such as direct and indirect stakeholders and the Shmemp! Includes the Nine-System Model and other unique tools for systems engineering